Consensus on diagnosis and empiric antibiotic therapy of febrile neurotropenia - Giulio A. Zanazzo; Nagua Giurici (MDPI AG, 2011)
Controversial issues on the management of empiric therapy and diagnosis of febrile neutropenia (FN) were faced by a Consensus Group of the Italian Association of Pediatric Hematology-Oncology (AIEOP). In this paper we report the suggestions of the consensus process regarding the role of aminoglycosides, glycopeptides and oral antibiotics in empiric therapy of FN, the rules for changing or discontinuing the therapy as well as the timing of the blood cultures.